Organizational social context and psychopathology of youth in residential care: The intervening role of youth caregiver relationship quality - Silva, Carla (2021)
Drawing on an ecological approach with multiple informants, this study investigated the mediating role of youth–caregiver relationship quality in associations between different features of residential care settings' organizational social context and youth's psychopathology. Participants were 378 youth aged between 12 and 25 years old, and 54 caregivers aged between 24 and 57 years old, from 29 generalist residential youth care settings in Portugal. Given the hierarchical structure of data, analyses were performed using multilevel modeling. Results revealed that organizational social contexts characterized by higher levels of engagement, stress, and centralization, as perceived by the caregivers, were associated with lower levels of youth's externalizing problems (e.g., aggressive behavior and delinquency), reported by the caregivers, via better youth–caregiver relationship quality, perceived by the youth in care. These findings highlight the relevance of creating an organizational social context in residential care settings that supports caregivers in establishing high-quality relationships with the youth in care, thereby promoting their mental health. This study contributes to the clarification of conflicting findings in previous studies of this field, by offering further empirical investigation of these issues.